Assessing knee strength ratios and bilateral deficit via dynamic vs. static tests in amateur rugby union players - Dobbs, I. J.; Watkins, C. M.; Barillas, S. R.; Wong, M. A.; Brown, L. E. (Isokinetics and Exercise Science, 2017)
BACKGROUND: Assessing players` leg strength ratios prior to season is important in order to measure performance and identify weaknesses. Leg ratios are calculated by dividing the moment of hamstring by quadriceps. The simple (concentric only) HQ ratio and the dynamic control ratio (DCR) (Hamstring eccentric/Quadriceps concentric) are used to detect asymmetry, knee strength, and bilateral deficit (BD). However, open (OKC) and closed kinetic chain (CKC) tests potentially provide different information regarding muscle strength and balance. OBJECTIVE: The purpose of this study was to measure the abovementioned ratios in male and female amateur rugby union players and to assess difference between OKC and CKC tests. METHODS: Six males (age = 22.00 ± 2.61 y, height = 172.67 ± 6.12 cm, mass = 80.28 ± 11.13 kg) and 11 females (age = 24.73 ± 3.66, height = 164.00 ± 5.23, mass = 74.00 ± 18.14 kg) rugby union players performed an isometric-mid thigh pull (IMTP) and isokinetic knee extension/flexion at 60 ° /s. RESULTS: The non-dominant leg simple ratio (0.81 ± 0.13%) was greater than dominant (0.74 ± 0.14%) while the DCR (0.81 ± 0.14%) was greater than simple ratio (0.73 ± 0.10%). The OKC BD (- 21.00 ± 13.86%) was significantly greater than its CKC counterpart (- 6.76 ± 9.79%) while males` OKC BD (- 30.55 ± 14.93%) was significantly greater than females` (- 15.79 ± 10.55%). CONCLUSION: The DCR may be more sport specific when measuring knee strength, while an OKC test is more likely to detect BD due to muscle isolation. ABSTRACT FROM AUTHOR